Contact Performance Numerical Simulation and Analysis of Gear Skiving - Chen Yongpeng; Xiao Lei (Jixie chuandong)
Gear skiving process has the advantages of high material removal rate, good forming accuracy and so on, and can realize the efficient machining of gears with special structure such as inner gears. It can effectively improve productivity and reduce cost by advancing the finishing process of gears. However, due to the presence of feed marks on the forming tooth surface, the contact performance of the tooth surface is not clear. In this study, firstly, according to the kinematic principle of gear skiving, a solid model of gears with non-smooth tooth surface is constructed. Then, the contact stress of non-smooth tooth surface is simulated by the finite element method, and the results are compared with the calculation results of the bearing capacity of gears recommended by international standards. Finally, the influences of feed and tooth modification coefficient on gear contact stress are analyzed. The results show that there is a nonlinear positive correlation between the contact stress and the feed. The tooth modification has little effect on the extreme value of contact stress, but has significant effect on the stress distribution area.